Thermal conductivity performance in sodium alginate-based Casson nanofluid flow by a curved Riga surface - Nagaraja, K. V.; Vinutha, K.; Madhukesh, J. K.; Khan, Umair; Singh Chohan, Jasgurpreet; Sherif, El-Sayed M.; Sarris, Ioannis E.; Hassan, Ahmed M.; Shanker, B. (Frontiers in Materials, 2023)
This study examines the effects of a porous media and thermal radiation on Casson-based nano liquid movement over a curved extending surface. The governing equations are simplified into a system of ODEs (ordinary differential equations) using the appropriate similarity variables.The numerical outcomes are obtained using the shooting method and Runge-Kutta Fehlbergs fourth-fifth order (RKF-45). An analysis is conducted to discuss the impact of significant nondimensional constraints on the thermal and velocity profiles. The findings show that the rise in curvature constraint will improve the velocity but diminish the temperature. The increased values of the modified Hartmann number raise the velocity, but a reverse trend is seen for increased porosity parameter values. Thermal radiation raises the temperature, while modified Hartmann numbers and the Casson factor lower the velocity but raise the thermal profile. Moreover, the existence of porous and solid fractions minimizes the surface drag force, and radiation and solid fraction components enhance the rate of thermal dispersion. The findings of this research may have potential applications in the design of heat exchangers used in cooling electronic devices like CPUs and GPUs, as well as microscale engines such as microturbines and micro-heat engines.